eInfoC mobile payment model and wap site prototype for sales of e-books - Shiratuddin, Norshuhada; Hassan, Shahizan; Zaibon, Syamsul Bahrin; Nur Salam, Sobihatun (ACM, 2006)
In this paper, we describe the process flow model in implementing mobile payment (mPayment) as the payment method for buying eBook. The model serves as a diagramatic representation of the processes that are involved. In addition, the WAP site features to browse eBook are also identified and produced to enable eBook Providers to market their products via mobile phones. Our study is based on and centred around an Electronic Information Centre (eInfoC) proposed and developed by researchers at Universiti Utara Malaysia.